2017
DOI: 10.21276/apalm.1126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Iron Deficiency Anemia on Glycated Hemoglobin (HbA1c) Levels in Diabetics with Controlled Plasma Glucose Levels

Abstract: Background: Glycated hemoglobin (HbA 1 C) is used as a gold standard for monitoring glycemic control. American Diabetes Association (ADA) has certified HbA 1 C ≥ 6.5% as a diagnostic criterion for diabetes mellitus (DM). Recent studies suggest that conditions affecting erythrocyte turnover like Iron deficiency anemia (IDA) alters HbA 1 C levels but their results are conflicting. However the effect of IDA on HbA 1 C is rarely reported.To determine the impact of IDA on HbA 1 C levels among controlled diabetics [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In a cross-sectional study, the mean HbA1c in patients with controlled diabetes with iron deficiency anaemia (IDA) was significantly higher than those without IDA (7.86 ± 0.11% vs 5.45 ± 0.038% [p<0.05]) and the HbA1c values were inversely proportional to total haemoglobin (p<0.05). [ 714 ] Further, significantly higher HbA1c levels are observed in patients with IDA than healthy individuals (5.51 ± 0.696 v/s 4.85 ± 0.461%, p<0.001) and the HbA1c levels significantly decline following iron supplementation (p<0.001). [ 35 ] Therefore, HbA1c results in diabetes patients with IDA should be interpreted carefully.…”
Section: R Ationale and E Videncementioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study, the mean HbA1c in patients with controlled diabetes with iron deficiency anaemia (IDA) was significantly higher than those without IDA (7.86 ± 0.11% vs 5.45 ± 0.038% [p<0.05]) and the HbA1c values were inversely proportional to total haemoglobin (p<0.05). [ 714 ] Further, significantly higher HbA1c levels are observed in patients with IDA than healthy individuals (5.51 ± 0.696 v/s 4.85 ± 0.461%, p<0.001) and the HbA1c levels significantly decline following iron supplementation (p<0.001). [ 35 ] Therefore, HbA1c results in diabetes patients with IDA should be interpreted carefully.…”
Section: R Ationale and E Videncementioning
confidence: 99%
“…In a cross-sectional study, the mean HbA1c in patients with controlled diabetes with iron deficiency anaemia (IDA) was significantly higher than those without IDA (7.86 ± 0.11% vs 5.45 ± 0.038% [p<0.05]) and the HbA1c values were inversely proportional to total haemoglobin (p<0.05). [ 714 ]…”
Section: R Ationale and E Videncementioning
confidence: 99%
“…Many relationship between IDA and HbA1c is a subject of research, with several studies suggesting that IDA is associated with higher HbA1c levels in diabetic and nondiabetic males and non-pregnant women, [31][32][33][34][35][36][37][38][39][40] while others propose a contrary association. [41][42][43][44][45] The literature contains different systematic reviews and meta-analyses that discuss the correlation between IDA and HbA1c levels in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients have a greater risk of developing a number of major health problems [11]. The incidence of diabetes is sharply increasing worldwide with many long-term macro-and micro-vascular complications [12,13]. The International Diabetes Federation reported that total number of diabetic subjects in India is 41 million in 2006 and that this would increase to 70 million by the year 2025 [14].…”
Section: Discussionmentioning
confidence: 99%